Anti‐proliferative effects of pentagamaboronon‐0‐sorbitol on HER2‐overexpressing breast cancer cells - Lailatul Qodria; Rohmad Yudi Utomo; Adam Hermawan; Edy Meiyanto (Universitas Gadjah Mada, 2022)
HER2‐positive breast cancer is an aggressive form of the disease that is associated with poor prognosis and chemo‐resistance. As such, investigation continues into the development of a new HER2‐targeted drug for breast cancer. This study investigated the anti‐proliferative activities of pentagamaboronon‐0‐sorbitol (PGB‐0‐So) in HER2‐overexpressing breast cancer (MCF‐7/HER2) cells. The cytotoxicity of PGB‐0‐So was assessed via MTT assay. Flow cytometry with propidium iodide and annexin‐V‐FITC staining was conducted to investigate the mechanism of PGB‐0‐So in inhibiting the proliferation of MCF‐7/HER2 cells. Finally, FACS analysis with 2′,7′–dichlorofluorescin diacetate staining was performed to examine intracellular ROS production. PGB‐0‐So exerted cytotoxicity towards MCF‐7/HER2 breast cancer cells with an IC50 value of 36 μM. PGB‐0‐So induced S‐phase arrest and apoptosis in MCF‐7/HER2 cells. Moreover, PGB‐0‐So could increase intracellular ROS production in MCF‐7/HER2 cells. PGB‐0‐So exerted anti‐proliferative activity towards MCF‐7/HER2 cells. This compound may be developed as a chemotherapeutic agent against HER2‐overexpressing breast cancer.